Evaluation of some microbial and botanical biopesticides against Helicoverpa armigera in chickpea (Cicer arietinum) - KHANNA, VEENA; CHEEMA, HARPREET KAUR; TAGGAR, GAURAV KUMAR (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted duing 2005–07 on the field efficacy of a native Bacillus thuringiensis (Bt) isolate from Punjab soils and a standard Bt formulation Halt 5 WP and neem seed kernel extract (NSKE) 5% against Helicoverpa armigera (Hübner) vis-à-vis recommended chemical insecticide endosulfan. The native Bt isolate (Bt C 5) was selected on the basis of its high delta- endotoxin concentration which was specific to the Lepidoptera pathotype. During the first year of study, the standard recommended insecticide -endosulfan 35EC @ 2. 5 litre/ha showed lowest larval population, followed by NSKE 5%, Halt 5 WP @ 1 kg/ha and Bt C 5. Pod damage was significantly low in case of endosulfan 35 EC; however, treatment of NSKE and Halt 5 WP were on par with endosulfan 35 EC. In the subsequent year, treatment of NSKE 5% + endosulfan 35 EC @ 1.25 litre/ha (half the recommended dose) showed the least larval population, followed by endosulfan @ 2.5 litre/ha alone. Pod damage was least in case of endosulfan 35 EC @ 2.5 l/ha, followed by NSKE 5% + endosulfan 35 EC @ 1.25 litre/ha. Similarly, highest grain yield was recorded in endosulfan 35 EC @ 2.5 litre/ha, followed by NSKE + endosulfan 35 EC @ 1.25 litre/ha, and Bt C 5 + endosulfan 35 EC @ 1.25 litre/ha, however, both were statistically at par.